Does increased trade openness enhance the impact of transport infrastructure investment on economic growth? - Miljković, Marko; Tanasković, Svetozar; Petrović Vujačić, Jelica; Vujačić, Ivan (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: This paper focuses on the impact of transport infrastructure investment on the economic growth of European countries, with a particular emphasis on analysing the effects of investment in both road and railway infrastructure in the first two decades of this century. The primary objective was to empirically test whether greater trade openness amplifies the positive effects of investment in transport infrastructure on economic growth. Methodology: The panel data analysis approach was employed for its numerous advantages over timeseries or cross-section analyses, encompassing a sample of 19 European countries from 2001 to 2021. Following the results of the applied econometric tests, models were estimated using generalised least squares (GLS) and ordinary least squares with panel-corrected standard errors (PCSE) methods. Results: The results revealed the positive impact of transport infrastructure investment on economic growth, with a pronounced significance associated with rail infrastructure investment, especially in the most developed countries. Road infrastructure investment only exhibited a positive impact in transition countries. Crucially, the analysis determined that the positive effects of investing in transport infrastructure on economic growth intensified with increasing trade openness. Implications and recommendations: The implications of the findings suggest that transport infrastructure investment alone is insufficient to drive economic growth. Other conditions must also be satisfied, particularly the economic integration of the country. Consequently, alongside transport infrastructure investment, it is essential to foster high levels of trade openness to ensure significant positive effects on the economy. Future research should further explore the significance of additional enabling conditions, such as a well-educated workforce and improved institutional environments, in facilitating and enhancing the positive effects of transport infrastructure investment. Originality/value: Given that the most significant investment in developing high-quality transport infrastructure within the European Union took place in the two first decades of this century, this research offers valuable insights through its empirical analysis of this period, deepening the understanding of the relationship between transport infrastructure investment and economic growth in Europe. The study’s value lies in identifying the particularly strong positive impact of investing in rail infrastructure in the most developed countries, alongside the positive influence of investing in road infrastructure, especially in transition countries where motorways comprise the largest share of investment projects. The originality of this research largely stems from its quantitative verification that increased trade openness enhances the positive effects of investing in transport infrastructure on economic growth.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 218-232
Keywords: transport infrastructure; investment; economic growth; trade openness